BENDING OF SUBMERGED WOODY RIPARIAN VEGETATION AS A FUNCTION OF HYDRAULIC FLOW CONDITIONS. (14th September 2011) - Stone, Mark C.; Chen, Li; Kyle McKay, S.; Goreham, John; Acharya, Kumud; Fischenich, Craig; Stone, Asako B.
ABSTRACT Woody riparian vegetation provides numerous ecological benefits such as stabilizing streambanks, storing and cycling nutrients, shading streams and providing habitat for wildlife. However, vegetation also increases hydraulic roughness and reduces the effective flow area, resulting in an increased water surface elevation for a given streamflow. Balancing the desire to preserve woody vegetation in stream corridors with the need to manage flood risks requires accurate techniques for predicting the influence of vegetation on stream hydraulics. However, this is a challenging problem because woody vegetation responds to the flow field itself by bending and streamlining in response to hydraulic forces. The goal of this study was to predict the bending behaviour of woody riparian vegetation as a function of hydraulic flow conditions. Field tests were performed to elucidate tree biomechanical properties for select riparian taxa of the southwestern USA. Biomechanical results served as input parameters for a numerical algorithm designed to predict tree bending for water velocities likely to be encountered during flood events. Bending simulations revealed appreciable variability in bent tree heights. Variability was likely a manifestation of the extensive variance in plant characteristics and properties inherent in biological specimens. However, no trees were expected to bend to a height lower than approximately 42% of their original height, even in water moving at 2.5 m·s‐1. The results of this work provide an important first step in an effort to predict a dynamic hydraulic roughness for vegetated channels and floodplains under flood conditions. Copyright © 2011 John Wiley & Sons, Ltd.